Effect of Tocotrienols on Lipid Profile in Rabbits - Uzma Shahid (Journal of Rawalpindi Medical College, 2012)
Background: To evaluate the effect of tocotrienols on serum lipids in cholesterol-fed rabbits. Methods: In this experimental study, thirty six, male New Zealand white rabbits were randomly allocated to three equal groups. They were given either normal rabbit diet (Group-I); or 2% high cholesterol diet (Group-II); or 2% high cholesterol diet with tocotrienols 6mg/kg body weight/day (Group-III) orally for six weeks. Serum lipid profile was analyzed at the start and end of study. Results: Baseline levels of serum lipids were not statistically different among the three groups (p>0.05). By the end of experiment, Group-I showed insignificant changes (p>0.05) while Groups-II&III exhibited significant increase (p<0.001) in serum levels of total cholesterol, LDLC, HDL-C and triglyceride in contrast to their baseline levels. However, serum total cholesterol, LDL-C and triglyceride levels were 27% (p<0.05), 29% (p<0.05), 13% (p>0.05) lower respectively and HDL-C concentrations were 4% higher (P>0.05) in tocotrienols-supplemented group compared with rabbits using only high cholesterol control diet. Conclusion: Tocotrienols may be therapeutically helpful as cholesterol lowering agents.